2021
DOI: 10.5001/omj.2021.56
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Valerian on Sleep Quality, Depression, and State Anxiety in Hemodialysis Patients: A Randomized, Double-blind, Crossover Clinical Trial

Abstract: Objectives: Our study sought to determine the effects of valerian on sleep quality, depression, and state anxiety in hemodialysis (HD) patients. Methods: This randomized, double-blind, placebo-controlled, crossover clinical trial was conducted on 39 patients undergoing HD allocated into a valerian and placebo group. In the first phase of the study, group A (n = 19) received valerian and group B (n = 20) received a placebo one hour before sleep every night for a total of one month. Sleep quality, state anxiety,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
1
14
0
2
Order By: Relevance
“…In a similar study, Gammoh et al [58] reported that there are no differences between using valerian at a dosage of 600mg for two weeks and placebo in terms of improving sleep latency, wake after sleep onset, and sleep quality. Tammadon et al [59] demonstrated that valerian produces similar results to oxazepam, with both agents improving sleep quality from baseline. Based on their reports, the levels of satisfaction in patients treated with valerian was over 80%.…”
Section: Methodsmentioning
confidence: 99%
“…In a similar study, Gammoh et al [58] reported that there are no differences between using valerian at a dosage of 600mg for two weeks and placebo in terms of improving sleep latency, wake after sleep onset, and sleep quality. Tammadon et al [59] demonstrated that valerian produces similar results to oxazepam, with both agents improving sleep quality from baseline. Based on their reports, the levels of satisfaction in patients treated with valerian was over 80%.…”
Section: Methodsmentioning
confidence: 99%
“…Valerian, forsythia perforatum, passionflower, and hops are all considered sleep aids for insomnia patients in natural medicines, and valerian is often used in western countries to help sleep or for sedation. As early as the sixteenth century, Valerian Sencha was used in Europe to help sleep and prolong life, and the U.S. Food and Drug Administration has listed valerian as a food supplement, and its use is not contraindicated ( 5 ). Its volatile components are often considered to be its effect on insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Here, individuals given a 600-mg dose reported significantly lower levels of anxiety than those given placebo or a higher 1800 mg dose ( Kennedy et al, 2006 ). A similar dose in isolation (530 mg) significantly reduced state anxiety (as measure by the State-Trait Anxiety Inventory (STAI)) following 1 month’s supplementation in haemodialysis patients ( Tammadon et al, 2021 ). Anxiolytic effects have also been demonstrated following lower doses.…”
Section: Introductionmentioning
confidence: 99%